Social Capital and Relative Income Concerns: Evidence from 26 Countries - Justina A.V. Fischer; Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2007)
Research evidence on the impact of relative income position on individuals' attitudes and behaviour is sorely lacking. Therefore, using the International Social Survey Programme 1998 data from 26 countries this paper investigates the impact of relative income on 14 measurements of social capital. We find support for a considerable deleterious positional concern effect of persons below the reference income. This effect is more sizeable by far than the beneficial impact of a relative income advantage. Most of the results indicate that such an effect is non-linear. Lastly, changing the reference group (regional versus national) produces no significant differences in the results.
Keywords: Z13; I30; D31; 330; Relative income; positional concerns; social capital; social norms; happiness